Determinasi Keputusan Hedging Perusahaan Publik Sektor Pertanian 2013-2019 - Irfani Azzah Nabiilah (Jurnal Ilmu Manajemen, 2021)
A multinational company uses a determination of hedging decisions in international trade. The difference in currency values is a risk that will occur and minimize this risk using hedging. This research's independent variable is firm size, profitability, liquidity, growth opportunity, and leverage. The hedging is the dependent variable. This research used secondary data derived from annual financial reports by quantitative approach. The object used in this research is agricultural sector companies on Indonesia Stock Exchange in 2013-2019 with 11 companies as the sample. The data analysis technique used is logistic regression. This study indicates that profitability proxied by return on assets positively affects the company's hedging decisions. Meanwhile, growth opportunity calculated by using a comparison between the market value of equity and book value of equity, leverage proxied by the debt to assets ratio, liquidity proxied by the current ratio, firm size measured using the natural logarithm of total assets does not affect the company's hedging decisions. This research explains that companies with high profitability should do hedging activities to protect the company from adverse risks.